The Impact of Load Variations on The 300 W Pico-hydro Power Plants Parameters (Voltage, Current, Frequency and Generator Speed) - Hendri, Zulka; Seftiani, Yudia Meka; Abadi, Akbar; Wiharti, Wiwik; Herisajani, Herisajani; Yandri, Valdi Rizki; Haryadi, Yuda; Mayura, Yona (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
This research examines how load variations affect the performance of a pico-hydro power system, specifically focusing on voltage, current, frequency, and generator speed. Experiments were carried out through direct measurement under different load conditions. The findings reveal that as the load increases, the output voltage decreases due to higher circuit resistance, while the output current rises significantly. The generator frequency remains relatively stable under light loads but starts to fluctuate near full capacity, indicating the need for improved regulation. Similarly, the generator’s rotational speed declines with higher loads, signaling a performance limit. These results highlight the critical relationship between load changes and system performance, providing valuable insights to enhance the efficiency and stability of pico-hydro systems, especially for renewable energy applications in remote areas.